Unheard-of Curiosities : Concerning the Talismanical Sculpture of the Persians, the Horoscope of the Patriarkes, and the Reading of the Stars - Gaffarel, Jacques (Humphrey Moseley, 1650)
1650 English translation of Curiositez inouyes sur la sculpture talismaniquedes Persans (Paris, 1629), by Jacques Gaffarel (1601–1681), a renowned cabalist and Hebrew and Asian studies scholar. Included in the work are two large folding plates depicting “the Celestial Constellations expressed by Hebrew characters.” Gaffarel asserts that the letters of the Hebrew alphabet could be interpreted from the constellations and read as if a book. Digitized content includes title pages and folding tables.
Keywords: Talismans; Astrology; Occultism; Magic; Curiosities and wonders; Gaffarel, Jacques, 1601-1681